2019
DOI: 10.1002/nau.24168
|View full text |Cite
|
Sign up to set email alerts
|

What's in a name? Choosing a title for a female pelvic medicine and reconstructive surgery clinic: A prospective questionnaire

Abstract: Aims:A new multidisciplinary clinic specializing in female pelvic medicine and reconstructive surgery (FPMRS) opened at our institution. We sought to assess patient preference in naming this new center, and how readability and word choice informs these preferences. Methods: We prospectively surveyed patient preference in naming this new center, as well as patient knowledge and societal perception of pelvic floor disorders. This survey was distributed to female patients presenting to general urology and gynecol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(34 reference statements)
1
1
0
Order By: Relevance
“…A qualitative study of the psychological consequences of pelvic oor trauma after vaginal birth also reported that the women plunged in negative emotions, such as anxiety, stigma, and failure [24]. Another study showed that feelings of shame about the disease is the main factor why women do not see a doctor [25]. However, the women in the present study a rmed that they were eager to receive professional help.…”
Section: Discussionsupporting
confidence: 44%
“…A qualitative study of the psychological consequences of pelvic oor trauma after vaginal birth also reported that the women plunged in negative emotions, such as anxiety, stigma, and failure [24]. Another study showed that feelings of shame about the disease is the main factor why women do not see a doctor [25]. However, the women in the present study a rmed that they were eager to receive professional help.…”
Section: Discussionsupporting
confidence: 44%
“…This is similar to women who experienced pelvic floor trauma after vaginal birth [ 21 ]. A study showed that feelings of shame about the disease is the main factor why women do not see a doctor [ 22 ]. However, the women in the present study affirmed that they were eager to receive professional help.…”
Section: Discussionmentioning
confidence: 99%